THE PRINCIPLES OF BALANCE AND THE EMERGENCE OF HUMANITY AWARENESS IN ‘ALI AHMAD BAKĀTSĪR’S SALLĀMAH AL-QASS: ISLAMIC LITERARY PERSPECTIVE - Mahmudah Mahmudah (CMES (Center of Middle Eastern Studies), 2022)
The worship of a servant to God will fall short of perfection without paying attention and treating those around them with respect. ‘Ali Ahmad Bakātsīr, through Sallāmah al-Qass, told a young man who solely practices solitary worship in his daily life and then suddenly falls in love with a sweet-voiced entertainer girl who changes his life. This paper aims to show the principles of balance and their impact on raising humanity's awareness in the novel, which can be classified as a textual-formalistic puritan Islamic literary work from an Islamic literary perspective. The data collection was carried out based on the work literature study method. The data were obtained by carefully reading the figures’ words, thoughts, and attitudes leading to a predetermined formal object. The data analysis method used was the interpretive method. The principles of balance found in the novel are (1) balance between individual worship and social worship, (2) balance between physical and spiritual life, and (3) balance between worldly life and the hereafter. These principles raise humanity's awareness, namely (1) other people outside of oneself need to be considered, not abandoned, and (2) one should not justify the good or bad of the other by only looking at their outward actions. Thus, the three principles of balance proposed by 'Ali Aḥmad Bakāṡīr in Sallāmah al-Qass show Islamic values, which are expected to be a guide for the life of Muslims. This is because this work is a puritan Islamic literature committed to implementing Islamic teachings for its adherents or believer.